NSD3S stabilizes MYC through hindering its interaction with FBXW7. (22nd October 2019) - Gonzalez-Pecchi, Valentina; Kwan, Albert K; Doyle, Sean; Ivanov, Andrey A; Du, Yuhong; Fu, Haian
Abstract: The MYC transcription factor plays a key role in cell growth control. Enhanced MYC protein stability has been found to promote tumorigenesis. Thus, understanding how MYC stability is controlled may have significant implications for revealing MYC-driven growth regulatory mechanisms in physiological and pathological processes. Our previous work identified the histone lysine methyltransferase nuclear receptor binding SET domain protein 3 (NSD3) as a MYC modulator. NSD3S, a noncatalytic isoform of NSD3 with oncogenic activity, appears to bind, stabilize, and activate the transcriptional activity of MYC. However, the mechanism by which NSD3S stabilizes MYC remains to be elucidated. To uncover the nature of the interaction and the underlying mechanism of MYC regulation by NSD3S, we characterized the binding interface between both proteins by narrowing the interface to a 15-amino acid region in NSD3S that is partially required for MYC regulation. Mechanistically, NSD3S binds to MYC and reduces the association of F-box and WD repeat domain containing 7 (FBXW7) with MYC, which results in suppression of FBXW7-mediated proteasomal degradation of MYC and an increase in MYC protein half-life. These results support a critical role for NSD3S in the regulation of MYC function and provide a novel mechanism for NSD3S oncogenic function through inhibition of FBXW7-mediated degradation of MYC.